Impacted Maxillary Central Incisors: Surgical Exposure and Orthodontic Treatment: A Case Report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2019)
Maxillary central incisor impactions occur infrequently.Their origins include various local causes, such as odontoma, supernumerary teeth, and space loss. Supernumerary and ectopically impacted teeth are asymptomatic and found during routine clinical or radiological examinations. The surgical exposure and orthodontic traction of impacted right central incisor after removal of odontomas is presented in this report.Ban J Orthod & Dentofac Orthop, April 2017; Vol-7 (1-2), P.31-37